The Semantics of Motion Verbs in Russian - Maria Gepner (Baltic International Yearbook of Cognition, Logic and Communication, 2016)
Within the group of imperfective motion verbs in Russian there exists a further subdivision into determinate and indeterminate verbs. Traditionally the distinction is said to lie in the direction of motion the verbs encode: motion in one direction or in different directions. In this paper I am going to argue that this distinction is not enough. I will claim that determinate verbs encode singular eventualities and indeterminate verbs are pluractional. Thus in the normal case, imperfective verbs are plural predicates which include singular and plural events in their denotations, in the case of motion verbs, imperfective denotations are subdivided into a singular and a pluractional predicate.
Keywords: motion verbs; semantics; linguistics; russian language; verb groups; determinate verbs; indeterminate verbs